2013
DOI: 10.1007/s10549-013-2662-3
|View full text |Cite
|
Sign up to set email alerts
|

LOXL2 expression is associated with invasiveness and negatively influences survival in breast cancer patients

Abstract: Lysyl oxidase-like 2 (LOXL2) is associated with invasiveness and metastasis in breast cancer. We analyzed the prognostic impact of LOXL2 for breast cancer patients and investigated the role of LOXL2 in breast cancer cell lines. Immunohistochemical study of LOXL2 expression was done in samples from 309 patients. Survival analysis was performed using log-rank test and Cox regression hazard model. After identification of LOXL2 expression in breast cancer cell lines, we performed matrigel invasion and wound-healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 31 publications
6
86
0
1
Order By: Relevance
“…For instance, inhibition of LOX through pharmacological inhibition or injection with lysyl oxidase (LOX)-neutralizing antibodies reduced tumor metastasis from solid tumors (Levental et al 2009;Cox et al 2013;Pickup et al 2013). Similarly, studies using function-blocking antibodies to inhibit lysyl oxidase-like 2 (LOXL2) reduced collagen alignment and decreased tumor burden in a breast tumor xenograft (Grossman et al 2016); these antibodies have been associated with invasiveness and poor outcome in breast cancer (Ahn et al 2013). Higher LOXL2 levels are also associated with tumor invasion and poor outcome in pancreatic cancer patients and showed some efficacy in mouse models of PDAC (Park et al 2016).…”
Section: Disrupting the Gradientmentioning
confidence: 99%
“…For instance, inhibition of LOX through pharmacological inhibition or injection with lysyl oxidase (LOX)-neutralizing antibodies reduced tumor metastasis from solid tumors (Levental et al 2009;Cox et al 2013;Pickup et al 2013). Similarly, studies using function-blocking antibodies to inhibit lysyl oxidase-like 2 (LOXL2) reduced collagen alignment and decreased tumor burden in a breast tumor xenograft (Grossman et al 2016); these antibodies have been associated with invasiveness and poor outcome in breast cancer (Ahn et al 2013). Higher LOXL2 levels are also associated with tumor invasion and poor outcome in pancreatic cancer patients and showed some efficacy in mouse models of PDAC (Park et al 2016).…”
Section: Disrupting the Gradientmentioning
confidence: 99%
“…LOX expression is often associated with specific tissues and biologic processes (9), and dysregulated expression was identified in many pathologic states (10)(11)(12). Elevated LOX expression is linked to the disrupted collagen morphology and increased tissue stiffness often found in tumors, leading to aberrant cellular behavior (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…Higher expression of LOXL2 was associated with poor outcome after a median follow-up time of 9.3 years. Moreover, preclinical and clinical data have clearly confirmed that the positive rate is higher in LOXL2 TNBC than non-TNBC tumors (Ahn et al, 2013).…”
Section: Prognostic Biomarkersmentioning
confidence: 87%